Academician S.R. Mirotvortsev (1878 - 1949) – the Clinical Physician, the Teacher, the Urologist Innovator (to the 140 anniversary since birth) - T. Sh. Morgoshiia (Vestnik Urologii, 2019)
The main milestones of life and S.R. Mirotvortsev’s creativity are given in article. The little-known facts from the biography of professor are noted. Rewarding with two gold medals for student’s works is analyzed: «Vessels and nerves of sinews of foot of the person» (in common with the student V.P. Vorobyov) and «Dislocations of bones of a wrist». It is noted that during the Russian-Japanese war spent 11 months in the besieged Port Arthur and remained with the wounded who were taken prisoner to Japanese there. From 1905 to 1914 worked in VMA at first under the leadership of professor S.P. Fedorov, then the assistant for professor V.A. Oppel. It is shown that since 1914 until the end of life worked in Saratov, occupying department of the general surgery, and since 1920 — faculty surgical clinic. From 1922 to 1928 the rector of the Saratov university. In the period of the Great Patriotic War was the chief surgeon of Saratov and the Saratov region. S.R. Mirotvortsev published about 150 scientific works on questions of clinical and field surgery. In work it is analyzed that he in 1908 offered original operation of change of ureters in a rectum, having defended the doctoral dissertation (1909) on this subject. It is noted that the broad popularity was gained by its researches about malignant new growths, in particular sarcomas of tubular bones. It developed methods of unilateral switching off of a large intestine, plasticity of a firm meninx the sealing gland, processing’s of burn wounds potassium permanganate solution. S.R. Mirotvortsev suggested to use haemostatic properties of a catgut for a local stop of bleedings from parenchymatous bodies and sine of a firm meninx. From numerous works on field surgery detailed statistical development of 180 thousand cases of a gunshot wound is especially valuable during World War I of 1914 — 1918. It is noted that the department of faculty surgery of the Saratov medical institute and the street in Saratov is called by the name of S.R. Mirotvortsev. It is awarded with awards of the Labour Red Banner, the Red Star and medals.